Prismatic dislocation- {11-21} twin interaction as a source of uncommon pyramidal-〈a〉 dislocation in HCP metals - Shuo Zhou; Peng Chen; Xiaohan Zhang; Bin Li; Hui-Yuan Wang (Materials Research Letters)
The interaction between prismatic dislocations and a [Formula: see text] twin boundary is systematically investigated using atomistic simulations. Interestingly, when the slip plane is parallel to the plane of shear, the parent prismatic dislocation is transmuted into a prismatic dislocation in the twin while the Burgers vector remains unchanged. In contrast, when the prismatic slip plane is inclined with the plane of shear, the prismatic dislocation is transmuted into the uncommon pyramidal-[Formula: see text] dislocation on the [Formula: see text] plane. The energetics during twin-slip interactions are quantified by Nudged Elastic Band calculations. Our results provide a new understanding in terms of twin-slip interaction in HCP metals.